2022
DOI: 10.1002/aur.2685
|View full text |Cite
|
Sign up to set email alerts
|

Altered medial prefrontal cortex and dorsal raphé activity predict genotype and correlate with abnormal learning behavior in a mouse model of autism‐associated 2p16.3 deletion

Abstract: 2p16.3 deletion, involving NEUREXIN1 (NRXN1) heterozygous deletion, substantially increases the risk of developing autism and other neurodevelopmental disorders. We have a poor understanding of how NRXN1 heterozygosity impacts on brain function and cognition to increase the risk of developing the disorder. Here we characterize the impact of Nrxn1α heterozygosity on cerebral metabolism, in mice, using 14 C-2-deoxyglucose imaging. We also assess performance in an olfactory-based discrimination and reversal learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…However, enhanced cognitive performance is detected in other mouse models of ASD with high construct validity. For example, enhanced learning is seen in various mouse models with ASD-related mutations, including Shank1 −/− 107 , Taok2 −/− 108 , Ctnbb1 −/– (Pvalb cell conditional) 109 , Nrxn1α +/− mice 110 and also in Aspm −/− mice that show reduced TRN Pvalb expression 111 . A recent publication reports that mice with an ASD-associated neuroligin-3 mutation also show enhanced ability in the rCPT 112 .…”
Section: Discussionmentioning
confidence: 99%
“…However, enhanced cognitive performance is detected in other mouse models of ASD with high construct validity. For example, enhanced learning is seen in various mouse models with ASD-related mutations, including Shank1 −/− 107 , Taok2 −/− 108 , Ctnbb1 −/– (Pvalb cell conditional) 109 , Nrxn1α +/− mice 110 and also in Aspm −/− mice that show reduced TRN Pvalb expression 111 . A recent publication reports that mice with an ASD-associated neuroligin-3 mutation also show enhanced ability in the rCPT 112 .…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with our finding that Shank2-KO mice were intact in reversal learning when only appetitive outcomes were used. However, numerous other studies found that reversal learning was impaired in various ASD model mice in the absence of an aversive outcome [16][17][18][19][20][22][23][24][25][26][27][28][29]. It is difficult to compare findings across studies because the studied genotypes and experimental procedures have varied widely.…”
Section: Discussionmentioning
confidence: 99%
“…People with ASD also show impairments in reversal learning, and their performance in reversal learning correlates with clinical ratings of restricted and repetitive behavior [14] and everyday symptoms of behavioral inflexibility [15]. Impaired behavioral flexibility has also been reported in mouse models of ASD [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Thus, a growing body of studies indicates that impaired behavioral flexibility is present and correlated with repetitive and restrictive behaviors in ASD, raising the possibility that repetitive and restrictive patterns of behavior associated with ASD might be manifestations of impaired flexibility.…”
mentioning
confidence: 99%
“…According to previous research [ 126 ], alterations in serotonin system function and the medial prefrontal cortex (PFC), as a result of 2p16.3 ( NRXN1 ), may contribute to some of the behavioral alterations; therefore, CNV increases the risk of developing neurodevelopmental disorders. They found, in mice, that reduced Nrxn1α expression induces prefrontal cortex hypometabolism and impairs cognitive flexibility.…”
Section: Biological Impacts Of Cnvsmentioning
confidence: 99%